Metaverse as future promising platform business model: Case study on fashion value chain - Saravanan Periyasami; Aravin Prince Periyasamy (Businesses, 2022)
The concept of a 'business model' refers to a collection of descriptions that highlight the most significant aspects of the business. The metaverse is already a reality that can be considered plausible; it is a digital world that can be accessed by various technologies, such as virtual or augmented reality, and it is a place in which people are able to communicate and collaborate with one another. Businesses are making an attempt to capitalize on a trend, since it is anticipated that the metaverse will become more decentralized in the near future because it provides outstanding possibilities for expanding business. In this article, we discuss a few aspects of the current business model, as well as the emergence of the metaverse and their influence in the existing business models, with emphasis on the fashion and retail industry. Users of the metaverse have the ability to personalize digital representations of themselves, known as avatars. These avatars may be utilized in virtual worlds, online games, and other types of online communities. The way advertising works in the metaverse is quite similar to how it operates in the real world. Because of this, there is a promising future in store for the future of marketing and advertising in the metaverse. The new virtual environment will inspire us to devise novel formulae and procedures, which will influence the user in previously unimaginable ways. In addition to that, the possibility of the metaverse becoming connected with generation Z (also known as gen Z) would be additional advantages that will help the company's bottom line in the decades to come.
Keywords: 650; industry 5.0; metaverse; business model; blockchain; gen Z; IoT; NFT; data economy; fashion; textile